Kangaroo method: perceptions of the nursing team in neonatal intensive therapy - Gabriela Vieira Mantelli; Márcia Rejane Strapasson; Aline Aparecida Pierotto; Jenifer Miguel Renosto; Juliana Fernandes Silva (Universidade Federal de Santa Maria, 2017)
Aim: this study aims at investigating the perceptions of a private hospital nursing staff on the Kangaroo Care practices applied to newborns hospitalized in the Neonatal Intensive Care Unit. Method: qualitative, exploratory and descriptive study, conducted at the Neonatal Intensive Care Unit a private hospital in Porto Alegre/RS. Fifteen professionals from the nursing team participated in the study and semi-structured interview was used. Results: four thematic categories emerged: the perception of the nursing team and the practice of Kangaroo Care; the difficulties found in the implementation of these practice; the benefits found after implementing the method; the contributions of neonatal nursing staff for the implementation of the method. Conclusion: the propose to implement Kangaroo Care method requires a change of paradigms on the humanized care of the premature and the underweight newborn.